A abordagem da didática desenvolvimental na formação do adolescente: ensino, aprendizagem e desenvolvimento na escola - Rodrigues, Iago de Souza (Brasil, 2024)
This article aims to understand the philosophical, psychological and pedagogical principles underlying developmental didactics, articulating them with the organization and mediation of teaching oriented towards the formation of adolescents. This is a study of a theoretical-bibliographical nature, based on authors such as Davydov (1987; 1988; 1998; 1999; 2017), Libâneo (2023), Libâneo and Freitas (2017; 2019), Anjos (2011; 2014; 2019), Puentes and Longarezi (2013), among others, in which we analyze developmental teaching, learned in the pedagogical and school training process, in favor of humanizing teaching practices, aimed at enabling the student to develop theoretical-scientific concepts through the task of study and their learning actions. In order to produce new meanings for teaching, which go beyond the infamous pedagogies of “learning to learn”, we seek to answer, according to the reality of school teaching, the following question, supported by Davídov (1988), about the didactics of teaching teacher: what educational possibilities can be formulated when we relate the principles of developmental didactics to adolescent school teaching, aiming to form new intellectual abilities or superior psychic qualities in the student? We therefore refer to developmental teaching as an alternative to overcoming the hegemonic educational practices that still prevail in the current Brazilian educational system, especially when aimed at teaching and learning adolescents.